One dimensional school rankings: A non-neutral device that conceals and naturalizes inequalities - Nata, Gil (2015)
Inequality has long been a central topic in the social sciences. The same holds true with regard to sociological research on education. In this paper we argue that, due to fairly recent developments in the managerialisation and marketisation of the educational field, often associated with the rise of neoliberalism, the topic of inequality gains new dimensions and accrued relevance. Rankings are a device associated with the processes mentioned above. They are instrumental in creating an educational market. Perhaps more importantly, they epitomize the attempt to use market regulation as an instrument for managing public policy. Based on quantitative research on secondary school rankings in Portugal, we provide evidence that school rankings are not as objective and neutral as it is often claimed. In addition, they conceal layers of the process of social construction of inequalities, thereby contributing to their naturalisation. This is particularly visible in the comparison of the differential between the scores obtained by students of private and public schools in their own schools and in national exams. We show that this differential is consistently higher in private (paid) schools than in public (free) schools. In an often fierce context of competition for access to limited places in higher education, these differences can make a difference. Inequalities are thus reinforced through procedural unfairness. Ultimately, we argue that rankings are mostly a device for allocating schools and students in a market, and not so much an analytical tool for explaining educational processes, or even assuring quality.